Influence of the tidal and rainfall cycles on the population structure and density of Mesacanthion hirsutum gerlach (nematoda, thoracostomopsidae) on a tropical sandy beach (Tamandaré Bay, Pernambuco, Brazil) - VENEKEY, Virág (2015)
The population structure (males, females and juveniles) and density of Mesacanthion hirsutum Gerlach were studied during the tides (low, flood, high and ebb) of two consecutive tidal cycles in four different months of the year (May, July, September and November). Mesacanthion hirsutum density variations showed association with the rainfall cycle, with lower densities during July and September and significantly higher values in May and November. The population structure was constituted mostly by juveniles indicating a continuous reproduction during all the studied period. There were no significant differences between light and dark periods of the day, however, the higher densities detected during the high and ebb tidal stages demonstrate that this species could be dispersing through the water column and/or migrating within the sediment.